Lactate-Induced Glucose Output Is Unchanged by Metformin at a Therapeutic Concentration – A Mass Spectrometry Imaging Study of the Perfused Rat Liver - Calza, Giulio; Nyberg, Elisabeth; Mäkinen, Matias; Soliymani, Rabah; Cascone, Annunziata; Lindholm, Dan; Barborini, Emanuele; Baumann, Marc; Lalowski, Maciej; Eriksson, Ove (Frontiers in Pharmacology, 2018)
Metformin is the first line drug for type 2 diabetes but its molecular mechanisms remain unclear. Here, we have studied the acute effect of a therapeutically relevant intrahepatic concentration of metformin on glucose production from lactate. We selected the perfused rat liver as experimental system since it enables the complete control of drug dosage. We used MALDI mass spectrometry imaging to estimate the concentration of metformin in the livers and we measured the concentration of glucose in the effluent medium under basal conditions and following lactate addition. MALDI mass spectra of thin sections of freeze-clamped rat liver perfused with metformin showed a peak at m/z 130.16 which was unambiguously assigned to metformin. The mass spectrometric detection limit was at a tissue concentration of about 250 nM, and uptake of metformin from the perfusion medium to the liver occurred with a Km of 0.44 mM. Metformin was evenly distributed in the liver irrespective of its concentration in the perfusion medium and the duration of a perfusion. At a parenchymal concentration of 30 µM, metformin did not induce any significant suppression of the basal or lactate-induced glucose release from the liver. These results show that MALDI-MSI can be applied to estimate the tissue concentration and distribution of metformin in a therapeutically relevant micromolar concentration range. Our findings challenge the view that metformin causes an inhibition of glucose release from the liver by inhibiting mitochondrial glycerol 3-phosphate dehydrogenase (EC 1.1.5.3).